2017
DOI: 10.1038/ng.3752
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide(1). We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 x 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples(2-7), while 4 (EEFSEC, DSP, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
311
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 323 publications
(321 citation statements)
references
References 80 publications
6
311
3
1
Order By: Relevance
“…One identified a novel variant near MAN2B1 that was associated with percent emphysema on computed tomography (CT) (16) and the other identified two loci that approached genome wide statistical 4 significance for COPD (13). This literature contrasts with that among persons of European ancestry, in whom GWAS have identified multiple loci in genes for lung function and COPD (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) To improve our current understanding of the genetic architecture of lung functionrelated traits in Hispanics/Latinos, we performed a meta-analysis for FEV1, FEV1/FVC, airflow limitation and COPD among six Hispanic/Latino groups in the HCHS/SOL cohort (10,32). Findings were replicated in European, Hispanic and African populations.…”
Section: Examination Of Genetic Risk Among Non-european Populations Mmentioning
confidence: 99%
“…One identified a novel variant near MAN2B1 that was associated with percent emphysema on computed tomography (CT) (16) and the other identified two loci that approached genome wide statistical 4 significance for COPD (13). This literature contrasts with that among persons of European ancestry, in whom GWAS have identified multiple loci in genes for lung function and COPD (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) To improve our current understanding of the genetic architecture of lung functionrelated traits in Hispanics/Latinos, we performed a meta-analysis for FEV1, FEV1/FVC, airflow limitation and COPD among six Hispanic/Latino groups in the HCHS/SOL cohort (10,32). Findings were replicated in European, Hispanic and African populations.…”
Section: Examination Of Genetic Risk Among Non-european Populations Mmentioning
confidence: 99%
“…Over the past decade, GWAS by the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) [7] and SpiroMeta consortia [8] have identified ~30 gene regions that contain common single nucleotide polymorphisms (SNPs) significantly associated with Forced Expiratory Volume in 1 second (FEV 1 ) and its ratio to Forced Vital Capacity (FEV 1 /FVC). GWAS approaches have also been used to identify genetic variants for COPD [5, 913]. Major candidate gene regions identified through GWAS of COPD include FAM13A [11], CHRNA3/5/IREB2 [9], and HHIP [13], with four novel loci, EEFSEC , DSP , MTCL1 , and SFTPD , that emerged in the most recently published GWAS of COPD [5].…”
Section: Genetic Studies Of Copd Support Sp-d As a Candidate Biomarkermentioning
confidence: 99%
“…In this issue of the European Respiratory Journal , Obeidat et al [4] identify surfactant protein-D (SP-D) as a potentially causal risk factor for COPD. The paper is presented in multiple distinct parts, beginning with a genome-wide association study to identify SNPs from three genomic regions (on chromosomes 6, 10 and 16) associated with circulating levels of SP-D, followed by a Mendelian Randomization study demonstrating that genetically determined lower levels of SP-D are associated with increased risk of COPD based on results from a large-scale consortium based on a Genome-wide association study (GWAS) of up to ~11,000 COPD cases and ~37,000 controls recently published by the International COPD Genetics Consortium (ICGC) [5]. The results from the study of Obeidat et al [4] are promising and open new potential avenues for early diagnosis and treatment of this disease.…”
mentioning
confidence: 99%
“…I will return to these later in the talk. A recent large GWAS for COPD published by Hobbs and associates 8 revealed a similar number of "hits"; 22 independent loci, 13 of which overlapped with the lung function-related susceptibility genes ( Figure 7). Again, no obvious biological pathways were evident, but HHIP was the most significant hit, and a lung protein Surfactant Protein D achieved the genome wide threshold; I will return to it as well.…”
mentioning
confidence: 90%
“…The NIH maintains an online catalog of GWAS results and as of 12 June 2017, the GWAS Catalog contained 2974 publications and 36,618 unique SNP-trait associations (https://www.ebi.ac.uk/gwas/). The list of traits and diseases, where one or more SNP have achieved the genome-wide threshold for significant association, includes hair color and freckles but also respiratory diseases and phenotypes including Asthma, 7 COPD, 8,9 Lung function, 10 CF disease severity 11 and IPF. 12 As a result, GWAS WORKS!…”
mentioning
confidence: 99%